Suitable Stimulation Technique to Record Visual Evoked Potential in Migraine Patients - Shushtarian, Seyed Mohammad Masoud (Journal of Ophthalmic and Optometric Sciences, 2020)
Abstract Background: Migraine is a very common primary headache disorder associated with intermittent attacks and great suffering. To deal with these patients, different diagnostic techniques may be used. Visual evoked potential (VEP) is one of useful techniques in this respect. Flash (F) and pattern reversal checkerboard (PRC) are two stimulating techniques to record VEP. The aim of present work is to compare these two techniques in migraine patients & look for the optimum technique. Material and Methods: Flash and pattern reversal checkerboard visual evoked potential was recorded in 20 migraine patients (with 40 eyes). The age range was 20 -30 years and BCVA was 10/10 in total subjects. Latency (msec) and amplitude (µv) of VEP, and P100 Peak were noted for each patient. The results obtained were compared together. Results: The mean latencies were 103.65 ± 11.89 and 112.07 ± 4.39 for pattern reversal checkerboard and flash stimulation, respectively. On the other hand, the mean amplitudes were 8.16 ± 1.60 and 8.34 ± 2.15 for pattern reversal checkerboard and flash stimulations, respectively. The VEP difference were significant (P < 0.001) for latency whereas the amplitude difference is not significant (P = 0.513), as far as two types of stimulations were concerned. Conclusion: From the present work results, one can conclude that pattern reversal checkerboard is a suitable technique to record VEP in migraine patients. Keywords: Migraine, Pattern reversal checkerboard visual evoked potential, Flash Visual evoked potential, Stimulation technique.